Structure and seismic hazard of the ventura avenue anticline and ventura fault, California : prospect for large, multisegment ruptures in the western transverse ranges - Hubbard, Judith (2014)
The Ventura Avenue anticline is one of the fastest uplifting structures in southern California, rising at ∼5  mm/yr. We use well data and seismic reflection profiles to show that the anticline is underlain by the Ventura fault, which extends to seismogenic depth. Fault offset increases with depth, implying that the Ventura Avenue anticline is a fault‐propagation fold. A decrease in the uplift rate since ∼30±10  ka is consistent with the Ventura fault breaking through to the surface at that time and implies that the fault has a recent dip‐slip rate of ∼4.4–6.9  mm/yr.